Biotechnological Approaches to Combat Mycetoma in Farmers: Impacts and Sustainable Solutions - Dey, Sreedeep; Roy, Arun (RADINKA JAYA UTAMA PUBLISHER, 2025)
Mycetoma, a chronic, gradually debilitating condition caused by fungi or bacteria, provides enormous challenges to agricultural communities, notably in West Bengal and Andhra Pradesh, India. This research investigates the socioeconomic and environmental effects of mycetoma on tobacco and tomato producers, where the disease is common due to overreliance on agrochemicals and poor soil management. Pilot studies in Cooch Behar have shown that climatic and soil conditions ideal for tobacco production may also lead to the spread of soil-borne infections, such as those that cause mycetoma. Current research indicates that creative biotechnology solutions—such as the production of genetically engineered crops, the use of biocontrol agents, and CRISPR-based gene editing—offer viable pathways for combating mycetoma. Furthermore, quick diagnostic methods and future vaccine development are crucial for early detection and prevention, which reduces farmers’ long-term socioeconomic burden. The significance of combining sustainable farming practices with these biotechnological developments cannot be emphasized, since they not only lower disease incidence but also encourage environmental preservation. Future research should focus on using genomic technology to better understand pathogen interactions in soil and developing immune-based treatments. This multidisciplinary approach will be critical in mitigating mycetoma’s impact, improving impacted farmers’ livelihoods, and promoting sustainable agriculture.